PERAN BNN KABUPATEN BULELENG DALAM PEMBERDAYAAN MASYARAKAT SEBAGAI NON PENAL POLICY DALAM UPAYA PREVENTIF PENYALAHGUNAAN NARKOTIKA DI KABUPATEN BULELENG - Corie Agung Patricia; landrawan, I Wayan; setianto, muhamad jodi (Jurnal Ilmu Hukum Sui Generis, 2024)
Agency (BNN) in empowering the community as a non-penal policy in the preventive effort against drug abuse in Buleleng District, and (2) analyze the inhibiting factors or obstacles faced by the Buleleng District BNN in optimizing community empowerment as a non-penal policy in the preventive effort against drug abuse in Buleleng District. The research used empirical legal research, with a descriptive research nature conducted at the Buleleng District BNN. Data collection techniques used were document study, observation, and interviews. Non-Probability Sampling technique was used for sample selection, and Purposive Sampling technique was used for subject determination. Data processing and analysis were conducted qualitatively. The results of the research indicate that; (1) Community Empowerment Programs carried out by the Buleleng District BNN are in accordance with the provisions of the laws and regulations. Buleleng District BNN's efforts in empowering the community as a non-penal policy in the preventive effort against drug abuse include the P2M Program through Socialization, Formation of Narcotics Activists or Volunteers, Rehabilitation Programs through the Formation of IBM Teams and Shining Villages, and Cross-Sectoral Cooperation. (2) There are obstacles in the implementation of community empowerment programs as non-penal policies in the preventive effort against drug abuse in Buleleng District, namely internal obstacles such as budget constraints, personnel/members, and transportation facilities, and external obstacles such as relatively low public awareness in the preventive effort against drug abuse.